Longitudinal vibration control for a suspension bridge subjected to vehicle braking forces and earthquake excitations based on magnetorheological dampers. (October 2016) - Yang, Meng-Gang; Cai, CS
In order to reduce the excessive longitudinal vibration of a suspension bridge induced by vehicle braking forces (as one of the possible dynamic loadings) and earthquake excitations, a mixed control methodology using magnetorheological (MR) dampers is developed in this study. Firstly, the corresponding preferred controls subjected to vehicle braking forces and earthquake excitations, separately, are obtained by simulation analyses for seven control strategies. Then, a mixed control system is established to obtain the best control efficiency and reduce the energy consumption of MR dampers, based on the displacement responses and changing rate of accelerations. Finally, this system is applied to reduce the longitudinal vibration responses of the Pingsheng Bridge. The numerical results show that the passive-on control and the semi-active fuzzy control are the corresponding preferred controls subjected to vehicle braking forces and earthquake excitations, respectively. The mixed control has a good agreement with the corresponding preferred controls under four dynamic loadings including the vehicle braking forces, the Pingsheng Bridge earthquake wave, the El Centro wave, and the Takochi-oki wave, which verifies the reliability and effectiveness of this system. The mixed control has good performance and applicability for different loading combinations composed of vehicle braking forces and earthquake excitations.